Public Relations Innovation in the Digital Era: Building Public Organizations' Reputations Through Social Media - Puspa Wardhani, Suryaningtiyas; Salsabila, Naila Rahma; Septia, Rizka; Romlah, Romlah; Wakhid, Ali Abdul (Nurul Jadid University, 2025)
The development of digital technology has changed the paradigm of public communication, particularly in the public relations practices of public organisations. The main challenge for public relations in the digital era is how to build and maintain an institution's reputation amid the rapid, dynamic flow of information. This study aims to analyse the forms of digital public relations innovation that utilise social media as a strategic space for building public reputation. The research method uses a descriptive qualitative approach, employing library-based research techniques to analyse literature, scientific journals, and digital documents related to public communication and reputation management. The results show that public relations innovation in the digital era encompasses three main aspects: transforming public relations from a communicator to a digital reputation manager, optimising social media for public dialogue, and using data analysis and information transparency to strengthen public trust. These innovations significantly enhance the legitimacy, credibility, and positive image of public institutions. Thus, digital public relations functions not only as a disseminator of information, but also as a participatory and strategic relationship manager in building organisational reputation in the digital era.